Over-Expression of ERF38 Gene Enhances Salt and Osmotic Tolerance in Transgenic Poplar - Cheng, Zihan; Zhang, Xuemei; Zhao, Kai; Yao, Wenjing; Li, Renhua; Zhou, Boru; Jiang, Tingbo (Frontiers in Plant Science, 2019)
Ethylene response factor (ERF) gene family plays an important role in abiotic stress responses. In this study, we isolated a salt-inducible ERF gene, ERF38 (Potri.006G138900.1), from the 84K poplar (Populus alba × P. glandulosa) and investigated its functions in salt and drought tolerance. We identified that ERF38 protein was targeted to nucleus and had no self-activation. Results from yeast-one-hybrid indicated that the ERF38 protein can specifically bind to the dehydration responsive element (DRE). We then successfully transferred the ERF38 gene into the 84K poplar. Under respective drought and salt stresses, four of the physiological traits, including peroxidase (POD) and superoxide dismutase (SOD) activities, soluble protein content, and proline content, increased significantly in the transgenic plants, compared to the wild type. Regarding the other two parameters, hydrogen peroxide (H2O2) and malondialdehyde (MDA) content, their increments in the transgenic lines under the stresses, which were compared to the water control, were significantly low than that of the wild type. In addition, reactive oxygen species (ROS) are scavenged in the transgenic lines under the stresses, but not in the wild type (WT). Interestingly, when challenged with the stresses, expression levels of a few genes associated with POD and SOD metabolism were significantly increased in the transgenic poplars. In all, evidence from morphological, physiological, and biochemical analyses indicated that over-expression of ERF38 gene can improve salt and drought tolerance in the transgenic poplar.